PENGEMBANGAN MEDIA KOLING STS (Komik Lingkungan Sehat dan Tidak Sehat) PADA MATA PELAJARAN IPA TEMA LINGKUNGAN UNTUK SISWA SEKOLAH DASAR - Faiz Mutiara Alfiya; Ferina Agustini; Fine Reffiane (Universitas Sarjanawiyata Tamansiswa, 2019)
This study aims to develop learning comic media that valid good environment and bad environment toward natural sciences learning in environment theme for class III elementary school.. Data collection instrument consicts of interview sheet, questionnaire on teacher needs, quesionnaire on student needs, Â quesionnaire on professional media valid, quesionnaire on material expert, quesionnaire teacher responses and quesionnaire students responses. Result from this study showed that data analysis, professional media valid and learning material expert indicate assessment of comic media with average of value professional media I is 91,67% and professional media II is 85% Â while result material expert I is 91,67% and maerial expert II is 85%. From that average result indicate that media is reasonable and valid for used to be learning media.